Effects of the extract and glycoalkaloids of Solanum lycocarpum St. Hill on Giardia lamblia trophozoites - Martins, Gilmarcio Z. [UNESP]; Moreira, Raquel R. D. [UNESP]; Planeta, Cleopatra da Silva [UNESP]; Almeida, Adelia E. [UNESP]; Bastos, Jairo K.; Salgueiro, Ligia; Cavaleiro, Carlos; Sousa, Maria do Ceu (Medknow Publications &media Pvt Ltd, 2015)
Background: Solanum lycocarpum has great importance for food and medicinal traditional use. Recently, it was also evidenced that extracts of S. lycocarpum St. Hill (Solanaceae) and its glycoalkaloids, solamargine (Sg) and solasonine (Sn), are active against flagellated protozoa. Objective: The aim was to assess the effects of the extract of S. lycocarpum and its glycoalkaloids, Sn, and Sg, on Giardia lamblia trophozoites. Materials and Methods: A crude extract (96% ethanol) (EB) of fruits of S. lycocarpum was prepared and fractionated by partition with 40% ethanol and n-hexane: Ethyl acetate. Glycoalkaloids, Sn, and Sg were recognized in the ethanol fraction (EF) and further isolated by column chromatography. EB, EF, the isolated Sn and Sg and a mixture (1: 1) of both glycoalkaloids were tested on cultures of G. lamblia trophozoites and macrophages. Results: EB, EF and glycoalkaloids of S. lycocarpum showed activity against Giardia (95.0 < Inhibitory concentration 50 [IC50] <= 120.3 mu g/mL). The mixture of glycoalkaloids (1: 1) was more active (IC50 = 13.23 mu g/mL) than each one individually, suggesting a synergic effect. Moreover, the mixture is nontoxic to macrophage cells. Conclusion: Results are optimistic concerning the anti-Giardia potential of the mixture Sn + Sg. Further studies, in vitro and in vivo, will be required to consolidate the usefulness of the mixture of Sn + Sg in view of a new therapeutic strategy for giardiasis.
Keywords: Giardia lamblia; Glycoalkaloids; Solamargine; Solanum lycocarpum; Solasonine